MR Angiography of the Head/Neck Vascular System in Mice on a Clinical MRI System. (29th May 2019) - Reimann, Carolin; Brangsch, Julia; Adams, Lisa Christine; Thöne-Reineke, Christa; Hamm, Bernd; Makowski, Marcus Richard
Abstract : Background . Magnetic resonance angiography (MRA) represents a clinical reference standard for the in vivo assessment of the vasculature. In this study, the potential of non-contrast-enhanced and contrast-enhanced angiography of the head/neck vasculature in mice on a clinical MR imaging system was tested. Methods . All in vivo magnetic resonance imaging was performed with a 3T clinical system (Siemens). Non-contrast-enhanced (time-of-flight, TOF) and contrast-enhanced angiography (gadofosveset-trisodium, GdT) were performed in C57BL/6J mouse strain. Lumen-to-muscle ratios (LMRs) and area measurements were assessed. Histology was performed as reference standard of all relevant vascular structures. Results . A close correlation between TOF ( R 2  = 0.79;p < 0.05 ) and contrast-enhanced (GdT) angiography ( R 2  = 0.92;p < 0.05 ) with histological area measurements was found. LMRs were comparable between both sequences. Regarding interobserver reproducibility, contrast-enhanced (GdT) angiography yielded a smaller 95% confidence interval and a closer interreader correlation compared to non-contrast-enhanced (TOF) measurements (−0.73–0.89; R 2  = 0.81 vs. −0.55–0.56; R 2  = 0.94). Conclusion . This study demonstrates that non-contrast-enhanced and contrast-enhanced angiographies of the head/neck vasculature of small animals can reliably performed on a clinical 3T MR scanner. Contrast-enhanced angiography enables the visualization of vascular structures with higher intravascular contrast and higher reproducibility.